Makna Hidup pada Wanita Dewasa yang Terlambat Menikah - DR, Maqhfirah (JURNAL DIVERSITA, 2018)
This research was a qualitative research regarding the meaning of life for unmarried woman. There are four components that were explored, the causes and psychological effect they experienced, coping strategy that used and the meaning of life that was owned by those women. The technique for collecting data using interview and observation sheet. The respondents was above 40 years old and unmarried. This research was supported by logotherapy theory of Victor Frankl. The meaning of life for these respondents was a kind of full life experiences that came from their suffering of being not married yet. The result of the this research showed thet the factors affecting both respondents had not get married because they want to be established before get married, dedication to their parents, and having a high standard factors. But for respondent I, study oriented factor and difficulty of married was also of factors. Both respondents enjoyed their unmarried status became they have freedom and autonomy in determining this own decision. But they have negative effect such as difficulty to fulfill their sexual need and difficulty when they got sick wothout any help from other people and feeling uncomfortable because of the norms from their religion and culture which considered unmarried woman as unlucky and incomplete as a woman.